The impact of technology on children's culture - Al-Awbthani, Miead Abdullah Mubarak (Journal of Educational and Psychological Sciences, 2022)
The culture of the child is one of the most important matters that occupy the interest of contemporary societies, and it is not isolated from the global changes that the world is witnessing today, the developments in technology have raised many concerns and raised a lot of controversy about the cultural and social risks resulting from the contents of this technology, which come to us in the form of programs, classes, games, and video and audio materials imported from the West. Modern technology has changed the environment in which our children live from that in which we and our parents lived, if these means have changed our way of life and our relationship with family and friends, how will new generations living in an environment of more sophisticated information media and means not be measured by our present and what will happen to the characteristics and identities that we think of today? Children are among the most vulnerable segments of society to social and cultural changes, these technologies will provide children with windows to view the world, and from the above we can ask: What is the impact of technology on children's culture.
Keywords: child; technology; culture; child culture